Promoting oral HIV self‐testing via the internet among men who have sex with men in China: a feasibility assessment. Issue 5 (18th December 2019) - Wang, X; Tang, Z; Wu, Z; Nong, Q; Li, Y
Abstract : Objectives: The HIV prevalence among Chinese men who have sex with men (MSM) is high, while the HIV testing rate is low. HIV self‐testing (HIVST) is a promising means of scaling up HIV testing among MSM in China, as the ability to test in private is appealing to many individuals. We evaluated the feasibility of promoting oral HIVST via the internet in the MSM population. Methods: From April 2013 to April 2014, MSM in two major cities in China were recruited for an observational study with assessment at baseline and follow‐up. Data were collected via questionnaire, oral HIVST, and clinic‐based HIV confirmatory testing. Results: A total of 510 MSM were recruited at baseline and 279 (54.7%) returned for a clinic follow‐up visit. Compared to MSM recruited via peer referral, those recruited via the internet were better educated, had a higher monthly income, sought and met male sex partners online more frequently, had less often tested or orally tested for HIV before, and being more likely to seek HIV knowledge or HIV intervention information online. The sensitivity of oral HIVST among MSM recruited via the internet was 92.9%, and the specificity was 96.8%. A total of 19.0% of MSM sought both male sex partners and HIV intervention programmes online. The associated factors were > 10 past male sex partners and ever testing for HIV using an oral self‐test kit. All MSM who were followed up re‐administered oral HIVST, yet fewer MSM recruited via the internet accepted blood retesting than other MSM. Conclusions: Promoting oral HIVST via the internet could be a feasible and promising approach to facilitate HIV testing among MSM in China.